Facet Joint Injection Role to Alleviate Lumber Back Pain - الرستم, فاتن; الشلق, عبد الله (Latakia University Journal -Medical Sciences Series, 2021)
Background& Objective. Lumbar facet joint constitutes a common source of pain, and is an enormous burden and cost generator for society. Lumbar facet joints constitute a common source of pain accounting for 15–45% of low back pain. Facet block is a procedure used in patients with facet arthrosis in which several other medical techniques have failed. Facet joint degenerative osteoarthritis is the most frequent form of facet joint pain. Diagnostic positive facet joint block can indicate facet joints as the source of chronic spinal pain. In our country, there is no evidence or studies regarding its efficacy, thus the interest in its demonstration. The purpose of this review is to describe the anatomy, epidemiology, clinical presentation, and radiologic findings of facet joint syndrome. Specific interventional facet joint management will also be described in detail. Materials & Methods: We made cohort prospective study included fifty consecutive patients with chronic low back pain treated with facet joint injection. Patients ages range between 30-80year old, the injection was done in Al Mouwasat University Hospital, Clinical assessments were carried out at a baseline after a 6-month follow-up visit using the visual analog scale for pain, Oswestry Disability Index for disability-specific measure and Macnab criteria for global effectiveness, and compared through analysis using paired-samples “t” tests. Results: After a 6-month follow-up, thirty-five patients (70%) showed a clinically significant reduction of pain and twenty-seven (60%) reported a clinically significant improvement of disability. Conclusion: facet joint injection reduces low back pain and disability of patients with unresponsive low back pain. The results support the need of a multidisciplinary approach for presurgical evaluation of patients with chronic pain.